Impacts of COVID-19 on value chains: findings and syntheses - CGIAR Research Program on Policies, Institutions, and Markets (2021)
Having a clear understanding of the impacts of the pandemic on value chains will assist policy makers in designing appropriate policies targeted at the different categories of value chain actors. For some of the studies, data analysis is still ongoing.